PENGEMBANGAN BUKU CEKAWAN (CERITA PUNOKAWAN) UNTUK SISWA SEKOLAH DASAR - Nova Sulistiani, Fana; Widiastuti, Sripit; Fauzi, Adin (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2022)
The teaching and learning process that takes place makes students easily bored and tend not to be interested in learning using the Javanese Gegladhen Book or hearing Punokawan stories from teachers, because they cannot read and see directly the description of the Punokawan storyline, thus causing the non-achievement of learning objectives. Based on the background that has been found, the formulation of the problem can be obtained as follows: How is the feasibility of learning resources. CEKAWAN Book (Punokawan Stories) for Elementary School Students? How do teachers and students read the learning resources of the CEKAWAN Book (Punokawan Story) for Elementary School Students? This research approach includes Research and Development (RD) research. According to (Sugiyono, 2016), Research and Development (RD) is a research method used to produce a particular product and test the effectiveness of the product. This research aims to produce or develop products. The product developed in this study is a learning resource in the form of a CEKAWAN Book (Punokawan Story) for Elementary School Students.This research refers to the research and development design of modifications of the development model according to Borg and Gall. The result of the research and development of the resulting product is the cekawan (Punokawan Story) book for elementary school students. The results of the validation of the feasibility of assessment learning resources from 6 validators, Material experts 78.66%, Linguists 82.22%, and media experts 77.33% categorized as "FEASIBLE". The results of the readability trial of 10 students and 3 class teachers, class teachers 93.81%, students 97%, categorized as "FEASIBLE", and can be used as an additional learning resource for Javanese subjects in the Punokawan wayang story chapter.ABSTRAKProses belajar mengajar yang berlangsung membuat peserta didik mudah bosan dan cenderung tidak tertarik belajar menggunakan Buku Gegladhen Bahasa Jawa maupun mendengar cerita Punokawan dari guru, karena tidak bisa membaca dan melihat langsung gambaran jalan cerita Punokawan, sehingga menyebabkan tidak tercapainya tujuan pembelajaran. . Berdasarkan latar belakang yang telah ditemukan, dapat diperoleh rumusan masalah sebagai berikut: Bagaimana kelayakan sumber belajar Buku CEKAWAN (Cerita Punokawan) untuk Siswa Sekolah Dasar? Bagaimana keterbacaan guru dan peserta didik terhadap sumber belajar Buku CEKAWAN (Cerita Punokawan) untuk Siswa Sekolah Dasar? Pendekatan penelitian ini termasuk penelitian Research and Development (RD).Menurut (Sugiyono, 2016), Research and Development (RD) merupakan metode penelitian yang digunakan untuk menghasilkan produk tertentu dan menguji keefektifan produk tersebut.Peneleitian ini bertujuan untuk menghasilkan atau mengembangkan produk.Produk yang dikembangkan dalam penelitian ini adalah sumber belajar berupa Buku CEKAWAN (Cerita Punokawan) Untuk Siswa Sekolah Dasar.Penelitian ini mengacu pada rancangan penelitian dan pengembangan modifikasi dari model pengembangan menurut Borg and Gall. Hasil penelitian dan pengembangan produk yang dihasilkan adalah buku CEKAWAN (Cerita Punokawan) untuk Siswa Sekolah Dasar. Hasil validasi kelayakan sumber belajar penilaian dari 6 validator, Ahli materi 78.66%, Ahli bahasa 82.22%, dan Ahli media 77.33% dikategorikan “LAYAK”. Hasil uji coba keterbacaan 10 peserta didik dan 3 guru kelas, guru kelas 93.81%, peserta didik 97%, dikategorikan “LAYAK”, dan dapat dijadikan sumber belajar tambahan mata pelajaran bahasa Jawa bab cerita wayang Punokawan.